Reproductive performances of N'dama and West African Shorthorn cattle in the humid forest zone of Ghana - Osei, S.A.; Effah-Baah, K. (1989)
The reproductive performance of N'Dama and West African Shorthorn (WASH) are evaluated. Production records from 1980 to 1985 at Kumasi University farm were analysed. There were no significant differences between the two breeds in terms of birth weight, age at weaning, age at first calving, calving interval, and postpartum return. N'Dama calves were significantly heavier (P